1992
DOI: 10.1128/aem.58.11.3598-3604.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of sulfonated azo dyes and sulfanilic acid by Phanerochaete chrysosporium and Streptomyces chromofuscus

Abstract: Five "4C-radiolabeled azo dyes and sulfanilic acid were synthesized and used to examine the relationship between dye substitution patterns and biodegradability (mineralization to C02) by a white-rot fungus and an actinomycete. 4-Amino-[U-14Cjbenzenesulfonic acid and 4-(3-sulfo-4-aminophenylazo)-[U-'4Clbenzenesulfonic acid were used as representative compounds having sulfo groups or both sulfo and azo groups. Such compounds are not known to be present in the biosphere as natural products. The introduction of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(42 citation statements)
references
References 48 publications
2
35
0
5
Order By: Relevance
“…Th e fact that the toxicity of the treatment continued to decrease from Day 12 to Day 24 to control's value (when considering the confi dence interval) suggests that these metabolites suff er further transformation into fragments that are as nontoxic as natural fungal metabolites released by the mycelium. Th ese observations are consistent with the mechanism of Amaranth decoloration by T. versicolor proposed by Gavril and Hodson (2007b) and with the reports regarding the mechanism of degradation (Spadaro and Renganathan, 1994) and mineralization (Paszczynski et al, 1992) of various azo dyes by another member of the white-rot fungi family, Phanarochaete chrysosporium. Th ese researchers suggest that the dyes are reduced to smaller molecular mass compounds similar in structure to the compounds of fungal metabolism (Gavril and Hodson, 2007b) or to CO 2 and water (Paszczynski et al, 1992).…”
Section: Resultssupporting
confidence: 91%
“…Th e fact that the toxicity of the treatment continued to decrease from Day 12 to Day 24 to control's value (when considering the confi dence interval) suggests that these metabolites suff er further transformation into fragments that are as nontoxic as natural fungal metabolites released by the mycelium. Th ese observations are consistent with the mechanism of Amaranth decoloration by T. versicolor proposed by Gavril and Hodson (2007b) and with the reports regarding the mechanism of degradation (Spadaro and Renganathan, 1994) and mineralization (Paszczynski et al, 1992) of various azo dyes by another member of the white-rot fungi family, Phanarochaete chrysosporium. Th ese researchers suggest that the dyes are reduced to smaller molecular mass compounds similar in structure to the compounds of fungal metabolism (Gavril and Hodson, 2007b) or to CO 2 and water (Paszczynski et al, 1992).…”
Section: Resultssupporting
confidence: 91%
“…The biochemical pathway or pathways of azo dye biodegradation idare poorly understood. This [69] showed that P. chrysosporium mineralized many sulfonated azo dyes and that modification of the chemical structure of these dyes did not significantly influence their susceptibility to degradation. In contrast, S. chromofuscus was unable to mineralize aromatics with sulfo groups and both sulfo and azo groups [69].…”
Section: Research Perspectivesmentioning
confidence: 88%
“…This [69] showed that P. chrysosporium mineralized many sulfonated azo dyes and that modification of the chemical structure of these dyes did not significantly influence their susceptibility to degradation. In contrast, S. chromofuscus was unable to mineralize aromatics with sulfo groups and both sulfo and azo groups [69]. They also showed that peroxidase enzymes were involved in the initial azo dye biodegradation process [70].…”
Section: Research Perspectivesmentioning
confidence: 88%
“…Desulfonations of aromatic sulfonates in fungi have also been implied, because CO P from the ring carrying the sulfonate was released [112], or observed directly [113]. These reactions have been attributed to (extracellular) peroxidases [113,114], which sometimes lead to extensive destruction of the compounds involved, essentially as in the enzymic combustion of lignin [115].…”
Section: Fungal Peroxidases and Arenesulfonatesmentioning
confidence: 99%